Survival, causes of death, and risk factors associated with mortality in Barcelona HIV new diagnoses. 2001-2013 - Garriga, C; García de Olalla, P; Clos, R; Gorrindo, P; Garrido-Estepa, M; Caylà, J (European Centre for Disease Prevention and Control, 2014)
The antiretroviral treatment has supposed a decrease in HIV-related mortality. We assessed factors related to survival in HIV individuals. Causes of death (CoD) in HIV individuals were described. Abstract methods Deaths registered in the Census until 30.06.2013 and 2001-2012 new diagnoses from Barcelona HIV Register were included in the analysis. The CoD were obtained from Death Register. The CoD were classified in external (ICD-10: X), HIV-related (B20-B24, B44.9, C83.7 and C85.9) and non-HIV-related (other codes) causes. Mortality rate was calculated as follow-up person-year per 1000 and its 95% confidence interval (M; 95%CI). Association with mortality of socio-demographic, clinical and epidemiological variables were studied using Cox regression [hazard ratio (HR); 95%CI]. Abstract results Among 3533 new HIV diagnoses, 168 (5%) died (M:8.2; 95%CI: 6.9-9.4). CoD was available in 93 (55%). Among those, 43% died by non-HIVrelated causes (M:1.9; 95%CI:1.3-2.5); 42% by HIV-related causes (M:1.9; 95%CI:1.3-2.5), and 15% by external ones (M:0.7; 95%CI:0.3-1.0). Worse survival was observed in injecting drug users (IDU)(HR:4.7; 95%CI:2.9-7.7) and heterosexual (HTS) men (HR:2.4; 95%CI:1.4-3.9), Spaniards (HR:2.5; 95%CI:1.6-4.0), Gràcia district residents (HR:2.0; 95%CI:1.1-3.7), illiterate/primary education individuals (HR:1.5; IC95%:1.1-2.2), and <200 CD4 subjects (HR:1.8; 95%CI:1.2-3.0). HIV-related CoD were due to infections (48%): most common in men who have sex with men (MSM) (63%), followed by HTS women (60%). Non-HIV-related CoD were cancer (29%): more prevalent in men (32%), people with have secondary/university studies (39%) and HTS men (50%); cardiovascular diseases (22%): in HTS women (57%) and illiterate/primary education individuals (35%) and; liver diseases (19%): in IDU (37%). Abstract conclusion Mortality was associated with being IDU, HTS man, Spaniard, with low educational level and damaged immune system. CoD frequencies in HIVrelated and non-HIV-related were similar